MidHopRoute: a multiple path routing framework for load balancing with service differentiation in wireless sensor networks. (27th July 2006) - Jain, Neha; Madathil, Dilip K.; Agrawal, Dharma P.
We introduce a simple but novel multiple path routing protocol to improve overall network lifetime by spread the routing load over a large number of sensor nodes and preventing congestion. We establish multiple paths between the source–destination pairs and classify them based on their route length and residual energy levels. Based on the nature of queries, we assign time critical queries to shortest paths and dynamically adapt the path of non-critical queries to balance the excess load generated on shortest routes. The energy conservation results are demonstrated for both, a regular and random distribution of sensor nodes using an analytical framework as well as ns-2-based simulation.